Analysis method of lithium battery positive electrode materials based on LIBS technology

By using analysis methods and dopants based on LIBS technology in the analysis of the positive electrode materials of lithium batteries, the problems of low analysis accuracy and difficulty in excitation of samples are solved, and high-precision and rapid analysis results are achieved to meet the real-time needs of the industry.

CN115629057BActive Publication Date: 2025-04-29HANGZHOU PUYU TECH DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211282905.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-19
Publication Date
2025-04-29
Estimated Expiration
2042-10-19

AI Technical Summary

Technical Problem

The existing lithium battery positive electrode material element analysis methods have problems such as low analysis accuracy, difficulty in excitation of samples and data lag, which is difficult to meet the industry's immediate and rapid analysis needs.

Method used

Using an analysis method based on LIBS technology, the analysis accuracy and sample excitation ease is improved by designing new modeling methods and dopants such as anhydrous copper nitrate and graphite.

Benefits of technology

It significantly improves the analysis accuracy, simplifies the sample excitation process, reduces errors, and meets the industry's rapid analysis needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115629057B_ABST
    Figure CN115629057B_ABST
Patent Text Reader

Abstract

The present invention provides an analysis method for the cathode material of a lithium battery based on LIBS technology, including a modeling stage and an analysis stage. The modeling stage includes the steps of: (A1) obtaining multiple groups of standard samples and performing tablet pressing treatment, where the standard samples include the cathode material of the lithium battery and a buffer agent, and the buffer agent includes metal ions with known concentrations; (A2) using a LIBS analyzer to detect the M groups of standard samples after tablet pressing treatment, with each group of standard samples corresponding to N detections, and obtaining the light intensity values of the characteristic peaks corresponding to the metal ions and the elements to be measured in the k-th detection of the i-th group of standard samples; (A3) obtaining the correction coefficient corresponding to the j-th element to be measured in the i-th group of standard samples according to the light intensity values; (A4) obtaining the corrected light intensity value of the characteristic peak of the j-th element to be measured in the i-th group of standard samples; (A5) using the concentration C ij and its corresponding light intensity value I' ikj to establish a mapping relationship. The present invention has the advantages of high analysis accuracy and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to element analysis, and in particular to an analysis method for lithium battery positive electrode materials based on LIBS technology. Background Art

[0002] Ternary cathode materials (LiNi x Co y Mn (1-x-y) O2) as a new type of positive electrode material, its performance is better than single-component positive electrode materials such as lithium cobalt oxide and lithium manganese oxide. It not only meets the requirements of higher energy density, but also maintains excellent high-rate charge and discharge performance, meeting the stringent requirements of today's new energy vehicles for power battery performance. The precursor of the ternary positive electrode material is made of nickel, cobalt, and manganese sulfate as raw materials. An appropriate amount of precipitant is added to the reaction tank, and a certain pH value, temperature and stirring speed are controlled to form a mixed reaction. Then, an appropriate amount of lithium carbonate or lithium hydroxide is added to stir, mix, sinter, and other series of steps to form a ternary positive electrode material. In the above process, it is necessary to regularly and accurately detect the content of nickel, cobalt, manganese, and lithium so that adjustments can be made according to actual needs.

[0003] Currently, there are several ways to detect nickel, cobalt, manganese and lithium:

[0004] 1. Inductively coupled plasma atomic emission spectroscopy (ICP-OES) method. Although this method can detect multiple elements at the same time, it has large errors, expensive instruments, large amounts of consumables (carrier gas), high inspection costs, and complex sample pre-treatment procedures.

[0005] 2. EDTA titration method is used to measure cobalt, and precipitation method is used to measure nickel. These methods are cumbersome to operate, require complex reagents, and usually have a test cycle of 2 hours. They are not suitable for large-scale, long-term sample testing.

[0006] It can be seen that the existing analysis methods have a long analysis cycle, resulting in serious data lag, and it is difficult to meet the industry's immediate and rapid analysis needs.

[0007] Laser induced breakdown spectroscopy is a common technique for elemental analysis. The basic principle is: a pulsed laser beam (usually tens to hundreds of millijoules) is emitted by the laser through a focusing lens to the sample surface. A portion of the sample at the focus point absorbs the laser energy and generates plasma. A portion of the plasma emission light is collected by the optical fiber and transmitted to the spectrometer, which then splits this portion of the plasma emission light (continuous spectrum, atomic spectrum, and ion spectrum). The detector at the exit of the spectrometer detects the spectral signal and converts the spectral signal into a digital signal and transmits it to the computer for spectral analysis. Each element has its own characteristic spectral line. Therefore, the type of element is analyzed according to the wavelength of the atomic (ion) spectral line, and the concentration of the element can be analyzed according to the intensity of the spectral line, that is, quantitative analysis is performed.

[0008] When LIBS is applied to the detection of elements in ternary cathode materials, some technical difficulties will be encountered, such as:

[0009] 1. Using the original modeling method, the analysis accuracy is low;

[0010] 2. In order to obtain good sample repeatability, the powder samples of ternary cathode materials generally need to be pressed into tablets, but lithium battery materials are difficult to form by direct tablet pressing;

[0011] 3. Due to the physical and chemical properties of the sample itself, lithium battery ternary positive electrode materials are difficult to be directly excited. Summary of the invention

[0012] In order to solve the deficiencies in the above-mentioned prior art solutions, the present invention provides an analysis method for lithium battery positive electrode materials based on LIBS technology.

[0013] The objective of the present invention is achieved through the following technical solutions:

[0014] The analysis method of lithium battery positive electrode materials based on LIBS technology includes a modeling stage and an analysis stage, and the modeling stage includes the following steps:

[0015] (A1) obtaining multiple sets of standard samples and pressing them into tablets, wherein the standard samples include the lithium battery positive electrode material and a buffer, and the buffer includes metal ions with known concentrations;

[0016] (A2) Using a LIBS analyzer to detect M groups of standard samples after tableting, each group of standard samples corresponds to N tests, and obtaining the light intensity value I of the characteristic peak corresponding to the metal ion in the kth test of the i-th group of standard samples ik0 , and the light intensity value I corresponding to the characteristic peaks of D elements to be measured ik1 ,I ik2 …I ikD ,get , j = 1, 2…D, M, N, D are all integers greater than 2;

[0017] (A3) Obtaining the correction coefficient W corresponding to the jth element to be measured in the i-th group of standard samples according to the light intensity value ij; ;

[0018] , , C ij is the concentration of the jth element to be measured in the i-th group of standard samples, C i is the concentration of the element corresponding to the metal ion in the i-th group of standard samples;

[0019] (A4) Obtain the corrected light intensity value of the characteristic peak of the jth element to be measured in the i-th group of standard samples ;

[0020] ;

[0021] (A5) Using the concentration C of the jth element to be measured in the i-th group of standard samples ij And its corresponding light intensity value Establish a mapping relationship.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. High analysis accuracy;

[0024] The analysis accuracy is significantly improved by using the newly designed modeling method and analysis;

[0025] 2. Easy to inspire;

[0026] Through the dopant, the sample to be tested is easily excited;

[0027] If anhydrous copper nitrate is used as the dopant, it is kept in a state without crystal water to prevent water molecules from absorbing laser energy, and it is convenient to accurately know the concentration of Cu element. Graphite is scaly in microscopic form. Under a certain pressure, the scales will overlap layer by layer and be tightly bound by other substances, acting as an adhesive. The graphite content in the dopant should not be less than 50%, otherwise it will significantly reduce the bonding effect of the mixture. Anhydrous copper nitrate provides a large amount of easily excited metal elements, which increases the plasma electron density during the excitation process, while reducing the introduction of other types of ions and controlling variables. The mixture of laser and copper nitrate / graphite is not only a process of heat conduction, but also a process of ablation and plasma. The mixture absorbs laser energy and locally vaporizes, and the ablation product is mixed with the sample in the gas phase to undergo a microscopic chemical "combustion" reaction, which greatly increases the plasma temperature. The combination of the above materials can fully promote the excitation of lithium battery material plasma and effectively improve the element spectrum signal-to-noise ratio. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The disclosure of the present invention will become easier to understand with reference to the accompanying drawings. It is easy for those skilled in the art to understand that these drawings are only used to illustrate the technical solution of the present invention and are not intended to limit the scope of protection of the present invention. In the drawings:

[0029] Figure 1 is a simplified flow chart of the modeling phase according to an embodiment of the present invention;

[0030] Figure 2 is a simplified flow chart of the analysis phase according to an embodiment of the present invention;

[0031] Figure 34 is a simplified flowchart of the analysis phase according to an embodiment of the present invention. DETAILED DESCRIPTION

[0032] Figure 1-3 The following description describes the optional embodiments of the present invention to teach those skilled in the art how to implement and reproduce the present invention. In order to teach the technical solution of the present invention, some conventional aspects have been simplified or omitted. It should be understood by those skilled in the art that variations or substitutions derived from these embodiments will be within the scope of the present invention. It should be understood by those skilled in the art that the following features can be combined in various ways to form multiple variations of the present invention. Thus, the present invention is not limited to the following optional embodiments, but is only limited by the claims and their equivalents.

[0033] Example 1.

[0034] The analysis method of lithium battery positive electrode materials based on LIBS technology in an embodiment of the present invention includes a modeling stage and an analysis stage. Figure 1 As shown, the modeling stage includes the following steps:

[0035] (A1) obtaining multiple sets of standard samples and pressing them into tablets, wherein the standard samples include the lithium battery positive electrode material and a buffer, and the buffer includes metal ions with known concentrations, such as copper ions or potassium ions;

[0036] (A2) Using a LIBS analyzer to detect M groups of standard samples after tableting, each group of standard samples corresponds to N tests, and obtaining the light intensity value I of the characteristic peak corresponding to the metal ion in the kth test of the i-th group of standard samples ik0 , and the light intensity value I corresponding to the characteristic peaks of D elements to be measured ik1 ,I ik2 …I ikD ,get , j = 1, 2…D, M, N, D are all integers greater than 2;

[0037] (A3) Obtaining the correction coefficient W corresponding to the jth element to be measured in the i-th group of standard samples according to the light intensity value ij ; ;

[0038] , , C ij is the concentration of the jth element to be measured in the i-th group of standard samples, C i is the concentration of the element corresponding to the metal ion in the i-th group of standard samples;

[0039] (A4) Obtain the corrected light intensity value of the characteristic peak of the jth element to be measured in the i-th group of standard samples ;

[0040] ;

[0041] (A5) Using the concentration C of the jth element to be measured in the i-th group of standard samples ij And its corresponding light intensity value Establish a mapping relationship.

[0042] In order to improve the analysis accuracy, further, Figure 2 As shown, the analysis phase includes the following steps:

[0043] (B1) mixing a powdered lithium battery positive electrode material with a dopant to obtain a mixture; the dopant includes graphite, copper ions and nitrate ions;

[0044] (B2) tableting the mixture;

[0045] (B3) Using a LIBS analyzer to detect the mixture after the tableting process, to obtain the content of the element to be measured in the lithium battery positive electrode material, wherein the element to be measured includes lithium and at least one of nickel, cobalt and manganese.

[0046] In order to reduce the difficulty of exciting the sample to be tested, further, the dopant includes anhydrous copper nitrate, the mass ratio of graphite to anhydrous copper nitrate is greater than 1 and less than 2.34; or, a mixture of potassium nitrate and copper sulfate.

[0047] In order to mix the sample to be tested uniformly, further, the mixture is prepared in the following manner:

[0048] The lithium battery positive electrode material and the dopant are placed in a ball mill and mixed to obtain the mixture.

[0049] In order to improve the analysis accuracy, further, Figure 3 As shown, in step (B3), the method for obtaining the content of the element to be measured includes the steps of:

[0050] (C1) Obtain S groups of spectra of the sample to be tested by using the method of step (B2), each group of spectra includes T spectra and light intensity values ​​I ij , the spectrum contains characteristic peaks of copper and the element to be measured, and S and T are both integers greater than 2;

[0051] (C2) Using the light intensity value I of each element to be measured in each set of spectra ij and the mapping relationship, obtaining the initial content of each element to be measured corresponding to the first group of spectra;

[0052] (C3) processing the initial content, the copper concentration in the sample to be tested, and the characteristic peak intensity values ​​corresponding to each element to be tested in the second group of spectra of the sample to be tested in accordance with steps (B3) to (B4) to obtain a corrected intensity value;

[0053] (C4) Based on the corrected light intensity value and the mapping relationship, the first correction content of each element in the sample to be tested is obtained.

[0054] In order to improve the analysis accuracy, the third group of spectra is further processed according to step (C3), the first correction content is used to replace the initial content, and then the second correction content is obtained by using the method of step (C4).

[0055] In order to reduce the complexity of the method, further, the dopant and the buffer are the same.

[0056] Example 2.

[0057] An application example of the analysis method for lithium battery positive electrode materials based on LIBS technology according to Example 1 of the present invention.

[0058] In this application example, Figure 1 As shown, the analysis method of lithium battery positive electrode materials based on LIBS technology includes the following steps:

[0059] (A0) Modeling stage, the specific method is as follows:

[0060] (B1) obtaining 6 sets of lithium battery positive electrode material standard samples, wherein the standard samples include the lithium battery positive electrode material with known lithium, nickel, cobalt and manganese concentrations and a buffer, which are mixed in a mass ratio of 1:1, and the buffer includes graphite and anhydrous copper nitrate in a mass ratio of 1:1, that is, the buffer contains copper ions with a known concentration;

[0061] The standard sample was obtained by mixing the lithium battery cathode material and the buffer in a zirconia ball mill, and then weighing 0.5 g of the standard sample and making a sample on a 13 mm die tablet press at a pressure of 15 tons;

[0062] (B2) Using a LIBS analyzer to detect 6 groups of standard samples after tableting, each group of standard samples corresponds to 8 tests, and obtaining the light intensity value I of the characteristic peak corresponding to the copper ion in the kth test of the i-th group of standard samples ik0 , and the light intensity values ​​I corresponding to the characteristic peaks of the four elements to be measured ik1 ,I ik2 …I ikD ,get , j = 1, 2…4;

[0063] (B3) Obtaining the correction coefficient W corresponding to the jth element to be measured in the i-th group of standard samples according to the light intensity value ij; ;

[0064] , , C ijis the known concentration of the jth analyte (lithium, nickel, cobalt and manganese) in the i-th set of standards, C i is the concentration of copper in the i-th group of standard samples;

[0065] (B4) Obtain the corrected light intensity value of the characteristic peak of the jth element to be measured in the i-th group of standard samples ;

[0066] ;

[0067] (B5) Using the concentration C of the jth element to be measured in the i-th group of standard samples ij And its corresponding light intensity value Establishing a mapping relationship, the method of establishing the mapping relationship is the prior art in this field;

[0068] (A1) In a pretreatment stage, a powdered lithium battery positive electrode material and a dopant are mixed in a mass ratio of 1:1, and the mixture is placed in a zirconia ball mill to obtain a mixture; the dopant and the buffer are the same;

[0069] (A2) tabletting the mixture: weighing 0.5 g of the mixture and pressing it on a 13 mm die tablet press at a pressure of 15 tons to make a sample tablet;

[0070] (A3) Analysis phase, including the following steps:

[0071] (C1) Using a LIBS analyzer to detect the mixture after tableting, four sets of spectra of the sample to be tested are obtained using the method of step (B2), each set of spectra includes 8 spectra and light intensity values ​​I ij , the spectrum contains characteristic peaks of copper and the element to be measured;

[0072] (C2) Using the light intensity value I of each element to be measured in each set of spectra ij and the mapping relationship, obtaining the initial content of each element to be measured corresponding to the first group of spectra;

[0073] (C3) processing the initial content, the copper concentration in the sample to be tested, and the characteristic peak intensity values ​​corresponding to each element to be tested in the second group of spectra of the sample to be tested in accordance with steps (B3) to (B4) to obtain a corrected intensity value;

[0074] The following table is a comparison between two light intensity processing methods in the prior art and the present invention, and the values ​​are relative errors;

[0075]

[0076] (C4) Based on the corrected light intensity value and the mapping relationship, the first correction content of each element in the sample to be tested is obtained.

[0077] Processing the third set of spectra according to step (C3), using the first calibration content to replace the initial content, and then using the method of step (C4) to obtain a second calibration content;

[0078] The fourth group of spectra is processed according to step (C3), the second correction content is used to replace the initial content, and the third correction content is obtained by the method of step (C4).

[0079] Example 3.

[0080] The application example of the analysis method of lithium battery positive electrode materials based on LIBS technology according to Example 1 of the present invention is different from Example 2 in that:

[0081] In the modeling calculations, potassium nitrate was used as the buffer, that is, potassium ions were utilized; the dopant used a mixture of potassium nitrate and copper sulfate (in a molar ratio of 2:1) instead of anhydrous copper nitrate, that is, it contained nitrate ions and copper ions.

[0082] The above embodiment only exemplifies that the mass ratio of graphite to anhydrous copper nitrate is 1:1, and the sample to be tested and the dopant are mixed in a mass ratio of 1:1. Of course, other ratios may also be used, such as the mass ratio of graphite to anhydrous copper nitrate is 1.2:1, 1.9:1, 2.34:1, and the sample to be tested and the dopant are mixed in a mass ratio of 2:1. These ratios can all achieve the purpose of the present invention.

Claims

1. An analysis method for lithium battery positive electrode materials based on LIBS technology, the analysis method for lithium battery positive electrode materials based on LIBS technology comprising a modeling stage and an analysis stage, characterized in that: The modeling phase includes the following steps: (A1) obtaining multiple sets of standard samples and pressing them into tablets, wherein the standard samples include the lithium battery positive electrode material and a buffer, and the buffer includes metal ions with known concentrations; (A2) Using a LIBS analyzer to detect M groups of standard samples after tableting, each group of standard samples corresponds to N tests, and obtaining the light intensity value I of the characteristic peak corresponding to the metal ion in the kth test of the i-th group of standard samples ik0 , and the light intensity value I corresponding to the characteristic peaks of D elements to be measured ik1 ,I ik2 …I ikD ,get , j = 1, 2…D, M, N, D are all integers greater than 2; (A3) Obtaining the correction coefficient W corresponding to the jth element to be measured in the i-th group of standard samples according to the light intensity value ij ; , , , C ij is the concentration of the jth element to be measured in the i-th group of standard samples, C i is the concentration of the element corresponding to the metal ion in the i-th group of standard samples; (A4) Obtain the corrected light intensity value of the characteristic peak of the jth element to be measured in the i-th group of standard samples ; ; (A5) Using the concentration C of the jth element to be measured in the i-th group of standard samples ij And its corresponding light intensity value Establish mapping relationship; The analysis phase includes the following steps: (B1) mixing a powdered lithium battery positive electrode material with a dopant to obtain a mixture; the dopant includes graphite, copper ions and nitrate ions; (B2) tableting the mixture; (B3) Using a LIBS analyzer to detect the mixture after the tableting process, to obtain the content of the element to be measured in the lithium battery positive electrode material, wherein the element to be measured includes lithium and at least one of nickel, cobalt and manganese.

2. The method for analyzing lithium battery positive electrode materials based on LIBS technology according to claim 1, characterized in that: In step (B3), the method for obtaining the content of the element to be measured includes the steps of: (C1) Obtain S groups of spectra of the sample to be tested by using the method of step (A2), each group of spectra includes T spectra and light intensity values ​​I ij , the spectrum contains characteristic peaks of copper and the element to be measured, and S and T are both integers greater than 2; (C2) Using the light intensity value I of each element to be measured in each set of spectra ij and the mapping relationship, obtaining the initial content of each element to be measured corresponding to the first group of spectra; (C3) processing the initial content, the copper concentration in the sample to be tested, and the characteristic peak intensity values ​​corresponding to each element to be tested in the second group of spectra of the sample to be tested in accordance with steps (A3) to (A4) to obtain a corrected intensity value; (C4) Based on the corrected light intensity value and the mapping relationship, the first correction content of each element in the sample to be tested is obtained.

3. The analysis method of lithium battery positive electrode material based on LIBS technology according to claim 2, characterized in that: The third group of spectra is processed according to step (C3), the first correction content is used to replace the initial content, and the second correction content is obtained using the method of step (C4).

4. The analysis method of lithium battery positive electrode materials based on LIBS technology according to claim 1, characterized in that: In the dopant, the mass ratio of graphite to anhydrous copper nitrate is greater than 1 and less than 2.

34.

5. The analysis method of lithium battery positive electrode material based on LIBS technology according to claim 1, characterized in that: The mixture is prepared by: The lithium battery positive electrode material and the dopant are placed in a ball mill and mixed to obtain the mixture.

6. The analysis method of lithium battery positive electrode material based on LIBS technology according to claim 1, characterized in that: The metal ions are copper ions or potassium ions.

7. The analysis method of lithium battery positive electrode materials based on LIBS technology according to claim 1, characterized in that: The dopant and buffer are the same.

Citation Information

Patent Citations

  • Method for analyzing content of main elements in nickel cobalt lithium manganate positive electrode material

    CN113311015A

  • Method for improving detection precision of portable LIBS (laser-induced breakdown spectroscopy) equipment

    CN114324301A